Subtle Changes of Basketball Player in Video Based Euler Method - Septian Enggar Sukmana; Nisa'ul Hafidhoh; Dwi Harini Sulistyawati (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Analysing basketball player movement is not performed conventionally recently. Combining science and technology in sport has made a great impact. Basketball player movement analysis using latest technology can achieved by many ways such as retrieving information from video. A video that contains basketball match can be valuable resource to be analysed by computer vision technique. Player movement estimation can be separated into two categories such explicitly or implicitly. Player movement estimation that is performed implicitly is assumed more efficient than explicitly one, but in consequent, it has exploiting series computation like Lagrangian or Eulerian to the pixel color value and it is not easy to be seen by human visual system. This paper uses Eulerian series because of its succest in the previous research activity that called eluerian video magnification technique. That technique is implemented to basketball player in the field and it is not easy task because it is the object is formed as group in certain environment.